2016
DOI: 10.1093/tropej/fmv097
|View full text |Cite
|
Sign up to set email alerts
|

Scrub Typhus: A Clinico-Laboratory Differentiation of Children with and without Meningitis

Abstract: Neurological involvement in the form of meningitis or meningoencephalitis, although well documented in scrub typhus, has not been extensively studied in the pediatric population. We report the clinical and laboratory profile of 96 children with scrub typhus and compared those with and without meningitis. Twenty seven (28%) children had clinical and laboratory evidence of meningitis. The most frequent presenting features were fever (100%), meningeal signs (66.6%), nausea and vomiting (56.3%), seizures (55.5%) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 21 publications
4
13
6
Order By: Relevance
“…The commonest presenting symptoms being high grade fever with chills, shortness of breath and myalgia, headache and jaundice which are in accordance to the earlier studies. 1,[10][11][12][13][14] The percentage of patients presenting with altered sensorium and seizures was 11.6% and the pathognomonic eschar was seen in 11.8% of the patients, which is similar to that in the previous studies. 1,10,[12][13][14] Thirty-seven patients had elevation of serum transaminases, without evidence of any multiorgan dysfunction.…”
Section: Resultssupporting
confidence: 78%
“…The commonest presenting symptoms being high grade fever with chills, shortness of breath and myalgia, headache and jaundice which are in accordance to the earlier studies. 1,[10][11][12][13][14] The percentage of patients presenting with altered sensorium and seizures was 11.6% and the pathognomonic eschar was seen in 11.8% of the patients, which is similar to that in the previous studies. 1,10,[12][13][14] Thirty-seven patients had elevation of serum transaminases, without evidence of any multiorgan dysfunction.…”
Section: Resultssupporting
confidence: 78%
“…The duration of fever and prodromal stage was significantly longer in the scrub typhus group and vice versa in the non–scrub typhus group composed of Japanese encephalitis, other viral encephalitides, cerebral malaria, dengue encephalopathy, etc, which are of acute or hyper-acute onset. Another pediatric study, however, concluded a similar duration of fever (8.4 days), 17,18 although an adult study reiterated our finding of a longer duration of fever in scrub typhus than bacterial meningitis. 19 However, fever duration as short as 3 days in scrub typhus has also been documented.…”
Section: Discussionmentioning
confidence: 51%
“…In the present study, cerebrospinal fluid protein level was significantly higher in the scrub typhus vs the non–scrub typhus group (110 vs 66.7). Other studies have reported moderately elevated protein, lymphocytosis, and normal glucose in the cerebrospinal fluid in scrub typhus meningoencephalitis, 8,18,19,30,32 although 1 study documented hypoglycorrhachia. 33 Longer duration of illness and elevated cerebrospinal fluid protein with lymphocytic pleocytosis makes tubercular meningitis the closest differential diagnosis in our setting.…”
Section: Discussionmentioning
confidence: 90%
“…Our findings were similar to other studies published in children from other parts of India. 5,7 Of various clinical features of meningitis, headache was noted in 62.5% and vomiting in 50% patients. Other pediatric studies have found headache in <50% children, though headache is seen in >60% of adults with STM.…”
Section: Discussionmentioning
confidence: 99%